UNIVERSAL ANDROID-BASED ATTENDANCE APPLICATION USING THE GEOFENCE METHOD - Samuel Prabowo; Rikip Ginanjar (President University, 2021)
Generally, companies usually apply attendance procedures using the fingerprint attendance machine every employee in the office without exception. A common problem that happens is in the marketing of employees who are more than once out of office in 1 day forget to do a presence that can affect salary reduction sanctions. As a solution to the problem, there should bepresence applications using Global Positioning System (GPS) technology and utilizing NFC (Near Field Communication) technology. By using this application, marketing personnel no longer need to perform a presence with fingerprints on the presence machine, but only need to carry a smartphone device equipped with GPS. The app works by recording employee attendance at the office location as an office entry status and recording the status outside of the office when the Marketing force leaves the office. In this system also implements the Geofence method as an indication of the radius in which the user can perform the attendance process